PELAKSANAAN PROGRAM WORKSHOP â€œBELAJAR EFEKTIFâ€ UNTUK ORANG TUA - Suprayekti Suprayekti; Septyara Dwi Anggraeni (Jurnal Ilmiah Visi, 2017)
This study aims to obtain a clear picture of the implementation of the â€œEffective Learningâ€ workshop programs for parents at Yayasan Rangkul Keluarga Kita which was held in November 2016-January 2017 in South Jakarta. This research uses a descriptive method with a survey technique. Data collection techniques used were direct observation, document observation, questionnaires, and interviews. The result of this study is description obtained from the implementation of learning â€œEffective Learningâ€ based on planning, implementation, and evaluation. In order for the learning process to work properly, facilitators involve learners to formulate workshop objectives.